Perennial philosophy in re-understanding Malay mythology and science of symbol - Ahmad, Baharudin (2010)
The intellectual discussion on Malay mythology, symbol and imagery have been almost completely forgotten by scholars and students of Malay studies presently and was very much misunderstood by scholars of Malay studies in the past. The modern Western approach which leaned toward the anthropological and sociological understandings of those aspects of Malay literary formulations have caused many grave misunderstanding and have considered them the various formulations due to the ignorance of the primitives. This paper will evaluate Malay mythology and the science of symbols from the perennialists point of view by taking into of consideration the various explanations made by scholars like Rene Guenon, Ananda Coomaraswamy, Frithjof Schuon, Martin Lings, and Seyyed Hossein Nasr regarding myths, symbols and imageries in traditional thought and literature. We believe those aspects of Malay literature require redefinitions and are in need of new light for a proper literary analysis.